Relationships between core strength, dynamic balance and knee valgus during single leg squat in male junior athletes - Nor Fatinah Affandi; Mohamad Saufi Zuhan Mail; Norain Mohd Azhar; Shazlin Shaharudin (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study was conducted to evaluate the relationships between core strength, dynamic balance and knee kinematics during single leg squat. Core strength helps to improve dynamic balance and muscle coordination between lower and upper extremities, as well as reduce injury risks and muscular strength imbalance. Dynamic balance is the ability to maintain a stable position during dynamic tasks and can be used as a predictor of injury risk factors. Thirty-two state-level male junior athletes with a normal range of dynamic knee valgus were recruited. The participants went through a series of tests that included Modified Plank Test, Star Excursion Balance Test (SEBT) and Single Leg Squat (SLS) test. Two-dimensional knee frontal plane projection angle (FPPA) during SLS was evaluated at a 60° knee flexion. There was a statistically significant correlation between distance reached in anteromedial direction and knee FPPA during SLS in the non-dominant leg (r = 0.374, p = 0.035). There was no significant correlation between duration of plank and knee FPPA during SLS in both dominant and non-dominant legs. The outcomes from this study are important to prevent lower limb injuries in male junior athletes.